THE CONCEPTUAL CHANGE ASSESSMENT BASED ON ESSAY QUESTIONS IN CASE STUDY OF DNA/RNA AND INTRON TOPICS - Kristianti, Tati; Widodo, Ari; Suhandono, Sony (Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
Most of the study on conceptual change was analysed using multiple-choice, true/false and true/false-reason type of questions. However, these questions are unable to reveal the variation in understanding of the university students. In this study, we developed a new conceptual change assessment based on essay questions. Here, student responses on DNA and intron term are presented as case studies in order to show the application of this assessment. The assessment is able to classify the various degree of understanding in university students such as construction, revision, complementation, static and disorientation. Our findings in university students studying DNA term showed that of 70 university students, 34% (construction), 36% (revision), 21% (complementation), 4% (static) and 5% (disorientation). On intron term finds construction (4%), revision (14%), static (44%) and disorientation (38%). Overall analysis using various categories of understanding reveals that DNA term is easier to understand by the university students than the intron term. This assessment is useful to evaluate the conceptual change level of university students in the class. Therefore, the assessment might also be useful to evaluate various teaching strategies and other topics.Keywords: conceptual change, essay, assessment, DNA, Intron